GOD HERMES AS THE MESSENGER ARCHETYPE - Ömer ALANKA (Fırat University, 2019)
This study reviews Hermes, the messenger of gods in the Ancient Greek Mythology as the messenger archetype. In addition to the messenger image, the Hermes persona contains commerce, robbery, and hermeneutics. Being a reflection of the mythical thought, the myth of Hermes is an important figure in mapping the mental patterns and an archetypal symbol in investigating the news and messenger typology. The myth of Hermes reveals the general view regarding the ancient period in understanding the meaning of the communication phenomenon in the Archaic period and the communication processes. Another focus point of the study is also the connection between the news and discourse in the Hellenistic period, where communication was also transformed into a part of the metaphysical process. While the collective unconscious and temporal bonds break off and form similar images and ways of thinking, Hermes becomes one of this collective unconscious samples as the messenger symbol. The concepts of news, discourse, and logos find the least common denominator with communication in the Ancient Greek culture. In this context, this study carries out a literature review regarding the communication in the ancient period and examines how the concept of messenger has been transformed into the collective unconscious in the example of God Hermes with an archetypal approach.